2000
DOI: 10.1111/j.1348-0421.2000.tb02525.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Frequencies of G Serotypes of Rotaviruses Recovered from Hospitalized Children with Diarrhea: A 10‐Year Survey (1987–1996) in Japan with a Review of Globally Collected Data

Abstract: Since rotavirus vaccines aim to protect children from severe diarrhea, knowledge of the prevailing G serotypes among rotaviruses from hospitalized children is essential. Thus, we determined the G serotypes of rotaviruses collected from children with acute diarrhea in a local referral hospital in Akita, Japan, over the 10-year period between January 1987 and December 1996. Based on the assumption that rotaviruses with an identical electropherotype possess the same G serotype, the G serotypes of 488 rotavirus-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
52
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 75 publications
0
52
1
Order By: Relevance
“…We recently reported that the relative frequencies of G serotypes of rotaviruses derived from Japanese children hospitalized with diarrhea over a 10-year period from 1987 to 1996 were 77.0 (G1), 14.5 (G2), 2.7 (G3) and 5.3% (G4), thus confirming the importance of G serotypes 1-4 (15). On the other hand, this study left the possibility that two rotavirus specimens (0.4%) that remained untypeable had G serotypes uncommon to human rotaviruses.…”
mentioning
confidence: 75%
“…We recently reported that the relative frequencies of G serotypes of rotaviruses derived from Japanese children hospitalized with diarrhea over a 10-year period from 1987 to 1996 were 77.0 (G1), 14.5 (G2), 2.7 (G3) and 5.3% (G4), thus confirming the importance of G serotypes 1-4 (15). On the other hand, this study left the possibility that two rotavirus specimens (0.4%) that remained untypeable had G serotypes uncommon to human rotaviruses.…”
mentioning
confidence: 75%
“…This was higher than the most recent national average rate of 3%, but was not significantly different (P ϭ 0.11) (8). The most common RV strains that have been globally associated with gastroenteritis are G1P [8] (6,11). These strains are significantly underrepresented in our area at rates of 16, 0, 1, and 3%, respectively (P Ͻ 0.05 for all).…”
mentioning
confidence: 96%
“…P specificity is more conservative than G specificity, with P [8] the most common type worldwide, followed by P [4] and P [6]. P [8] is most frequently associated with serotypes G1, G3, and G4, while P [4] is most frequently associated with G2 (6,11).…”
mentioning
confidence: 99%
“…Although 15 G serotypes have been described in the literature (12), G1 G4 were shown to be the G serotypes most frequently found in human rotaviruses (14). G9 human rotaviruses, however, emerged globally in the mid-'90s and thereafter, and these G9 strains were reported to predominate in some geographic settings (1,2,10,15).…”
mentioning
confidence: 99%